(untitled) (Research, Society and Development, 2020)
The classroom is composed of a great diversity of people with their own cultural background. Each individual has a way of learning and in recent years research that identifies these learning styles have emerged. A bibliographic review, aiming to identify variations in the learning styles of students from different knowledge fields: humanity, mathematics and biology, in order to assist in the development of strategies to make the teaching styles of teachers more flexible in training educational background, aiming at better expectations and future results. In general, the active and visual style was dominant in the exact and biological fields. In the humanities, there was a predominance of reflective style. Hybrid and weighted models with aspects related to the needs of each area can enhance students in the learning process. For teachers, knowing the learning styles of students can help in the development of strategies that increase motivation and improve the outcome of teacher-student interactions and can reflect positively on reducing dropout in technical schools.